Pengambilan Keputusan dan Personal Stiving untuk Bertahan Sebagai Biarawati yang Berkarir di Dunia Pendidikan: (Studi Kualitatif Fenomenologi di Kongregasi Biara Ursulin) - Enge Christina (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Nuns who pursue a career in education face unique challenges in making decisions and managing their personal striving in order to endure their vocation. This study aims to explore the experiences of nuns who face the dynamics of decision-making and personal striving in the context of their educational careers. A phenomenological approach was used to understand the subjective meanings of the nuns' experiences. The research method involved in-depth interviews with nuns who have a career in education in the Ursuline Convent Congregation. The qualitative data collected was analysed using the Interpretative Phenomenological Analysis (IPA) approach. The results showed that decision-making is coloured by internal factors, such as spiritual calling and religious identity, as well as external factors, such as pressure from the social environment and organisational demands. Meanwhile, the nuns' personal striving in this context is manifested in efforts to maintain loyalty to religious values, strengthen supportive interpersonal relationships, and develop professional competence in the field of education. The findings of this study provide valuable insights into the internal and external dynamics that influence nuns' decision-making and personal striving in pursuing their educational careers. The practical implications of the findings can be used to help inform formation and support programmes for nuns pursuing a career in education, as well as providing a foundation for further research in this area.